[Students in Sierra Madre dorm room, 1987] - Information Technology Services::::::photographer::: (1987)
The dorm room is decorated with a Top Gun poster, a Coronado Golf Course flag, and 'Go Navy' and 'I Love San Diego' stickers. Based on these decorations, the resident is presumed to be from San Diego.